Evaluating seasonal soil water dynamics using a simple soil water balance model in northern Ghana - Kadyampakeni, Davie M.; Ellis, Tim; Sidibe, Yoro (2016)
Soil water management is critical for sustainable crop production, particularly in drought-prone environments. A range of strategies can be used to address spatial (need to improve in-situ infiltration) and temporal (need to improve water holding capacity /storage) to increase soil water availability for crop water uptake and improved yield production and productivity. This paper presents the results from field studies of rainfall and run-off monitoring in rainfed maize-based cropping systems in northern Ghana. Rainfall was measured using rain gauges and run-off was estimated using run-off pits in selected fields plots. Long-term 20-year weather data were used in simulation experiments using a deterministic water balance model to represent smallholder rainfed maize crop system. The field studies in the three regions of northern Ghana resulted in the development of regression rainfall-runoff relationships with R2 in the range 0.75 to 0.97 for fields with/without in situ. Further, estimation of size of water conservation/storage structures could be designed based on long-term rainfall-runoff relations to increase timely crop water availability and reduce spatial losses of water through surface runoff.